Genetic architecture of carotid artery intima-media thickness in Mexican Americans - Melton, P.; Carless, M.; Curran, J.; Dyer, T.; Göring, H.; Kent, J.; Drigalenko, E.; Johnson, M.; MacCluer, J.; Moses, Eric; Comuzzie, A.; Mahaney, M.; et al. (2013)
Background: Intima-media thickness (IMT) of the common and internal carotid arteries is an established surrogate for atherosclerosis and predicts risk of stroke and myocardial infarction. Often IMT is measured as the average of these 2 arteries; yet, they are believed to result from separate biological mechanisms. The aim of this study was to conduct a family-based genome-wide association study (GWAS) for IMT to identify polymorphisms influencing IMT and to determine if distinct carotid artery segments are influenced by different genetic components. Methods and Results: IMT for the common and internal carotid arteries was determined through B-mode ultrasound in 772 Mexican Americans from the San Antonio Family Heart Study. A GWAS using 931219 single-nucleotide polymorphisms was undertaken with 6 internal and common carotid artery IMT phenotypes using an additive measured genotype model. The most robust association detected was for 2 single-nucleotide polymorphisms (rs16983261, rs6113474; P=1.60e−7) in complete linkage disequilibrium on chromosome 20p11 for the internal carotid artery near wall, next to the gene PAX1. We also replicated previously reported GWAS regions on chromosomes 19q13 and 7q22. We found no overlapping associations between internal and common carotid artery phenotypes at P<5.0e−6. The genetic correlation between the 2 carotid IMT arterial segments was 0.51. Conclusions: This study represents the first large-scale GWAS of carotid IMT in a non–European population and identified several novel loci. We do not detect any shared GWAS signals between common and internal carotid arterial segments, but the moderate genetic correlation implies both common and unique genetic components.